Targeting intermittent hypoxia downstream pathways for biomarker discovery and new treatment perspectives in cutaneous melanoma. Issue 2 (31st January 2019) - Minovès, Mélanie; Pépin, Jean-Louis; Godin-Ribuot, Diane
In addition to being an independent risk factor for cardiometabolic disease [1], obstructive sleep apnoea (OSA) is now recognised as promoting cancer development. Although experimental [2, 3] and clinical [4, 5] evidence for this association appeared only a few years ago [6, 7], rapid advances have been made in the gap of knowledge regarding the types of cancers promoted by OSA and the oncogenic pathways involved. Targeting the pathways induced by obstructive sleep apnoea-associated intermittent hypoxia could significantly improve biomarker discovery and new treatment perspectives in patients with cutaneous melanoma http://ow.ly/wF3J30nlzL4